How Accession to the European Union Has Affected External Trade and Foreign Direct Investment in Central European Economies - Kaminski, Bartlomiej (World Bank, Washington, DC, 2014)
The collapse of central planning set in motion the reintegration of the Central European countries into the world economy. The European Union (EU), because of its proximity, economic weight, and policy-induced deep integration, has shaped these countries' politics, and economics. The process of accession to the EU - which began with the signing of the European Association Agreements in 1991 - has influenced their economic institutions, policies, and performance. The author traces the emerging architecture of commercial relations in Europe, and argues that the accession process had its greatest impact on capital flows, and later on good flows. The countries that have benefited most from accession, are those that followed the path of radical liberal reform. Radical liberal reform, combined with preferential access to EU markets, attracted foreign direct investment. The European Union provided an outlet, initially for Central European countries' unskilled-labor intensive products, and more recently for skilled-labor intensive, and technology-based products. Knowledge-intensive imports from the European Union, have also contributed to industrial realignment in the Central European countries. The prospect of accession, and, since 1998, unfettered access to EU markets for industrial products, has given a boost to multinationals, relocating production in these countries.